[Rezension von: Ooi, Keat Gin, The Japanese occupation of Borneo, 1941-1945. Higuchi, Wakako,The Japanese administration of Guam, 1941-1944] - Melber, Takuma (De Gruyter Oldenbourg, 2019)
Rezension von: Ooi, Keat Gin: The Japanese occupation of Borneo, 1941–1945, London, New York: Routledge 2011, XXIII, 199 S. (= Routledge Studies in the Modern History of Asia, 65), ISBN 978‑0‑415‑45663‑0. - Rezension von: Higuchi, Wakako: The Japanese administration of Guam, 1941–1944. a study of occupation and integration policies, with Japanese oral histories. Forewords by Donald Denoon and Gotō Shinhachirō, Jefferson, NC, London: McFarland 2013, IV, 330 S., ISBN 978‑0‑7864‑3978‑2
In: Militaergeschichtliche Zeitschrift, 78 (2019), Nr. 1. pp. 296-302. ISSN 2193-2336 (Druck-Ausg.); 2196-685 (Online-Ausg.)
Keywords: Rezension